Eksperimentasi Model Pembelajaran Discovery Learning Berbasis Etnomatematika Pada Mata Kuliah Matematika Diskrit - Ratna Herawati; Ellen Proborini (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2026)
Higher education institutions are expected to produce graduates with strong academic competencies and higher-order thinking skills. However, learning outcomes in the Discrete Mathematics course of the Informatics Study Program remain relatively low due to the abstract nature of the subject matter and the dominance of lecturer-centered instruction. This study aimed to examine the effect of an ethnomathematics-based Discovery Learning model on students’ learning outcomes in Discrete Mathematics. A quantitative approach with a quasi-experimental design was employed. The sample consisted of 40 students selected through cluster random sampling, comprising 20 students in the experimental class and 20 students in the control class. Data were collected using a learning achievement test that had met validity and reliability requirements. Data analysis was conducted through normality, homogeneity, and t-tests. The findings revealed a significant difference between the learning outcomes of students taught using the ethnomathematics-based Discovery Learning model and those taught through direct instruction (tcount = 2.614 > ttable = 1.999). The mean score of the experimental group was 71.94, which was higher than that of the control group (61.37). These findings indicate that integrating Discovery Learning with ethnomathematics effectively improves students’ learning outcomes. The study implies that culturally responsive and contextual learning approaches can serve as innovative strategies to facilitate the understanding of abstract mathematical concepts while enhancing student engagement and active participation in higher education learning environments